2017
DOI: 10.4034/pboci.2017.171.02
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Metabolic Effects of two Periodontal Therapeutic Modalities in Diabetic Patients with Residual Pockets

Abstract: Objective: To evaluate the metabolic control and compare the clinical effects between non-surgical and surgical therapies on periodontal treatment of residual pockets of type 2 diabetic patients. Material and Methods: 352 periodontal sites in 16 type 2 diabetic subjects with residual pockets of similar depths were randomly selected, whose contralateral quadrants were divided into G1 and G2 undergoing surgical and nonsurgical therapy, respectively, and evaluated 3 and 6 months after the first intervention. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study conducted by Lucena et al, (2017) [22] , with the objective of assessing metabolic control and comparing the clinical effects between nonsurgical and surgical therapies in the periodontal treatment of residual bags of patients with DM2, reported that the mean values of Hb1Ac of patients were significantly reduced after surgical and non-surgical periodontal therapy, where both behaved similarly when compared to each other, but with greater effectiveness of surgical therapy in reducing the studied clinical parameters. The precise mechanisms that lead to HbA1c reduction and improved glycemic control after periodontal treatment in people with diabetes are not completely clear, but are presumed to arise from the combined effects of reduced systemic inflammation and reduced systemic bacterial challenge, leading to improvements in insulin resistance and insulin signaling (POLACK and SHAPIRA, 2018) [37] .…”
Section: Diabetes and Periodontitismentioning
confidence: 99%
“…A study conducted by Lucena et al, (2017) [22] , with the objective of assessing metabolic control and comparing the clinical effects between nonsurgical and surgical therapies in the periodontal treatment of residual bags of patients with DM2, reported that the mean values of Hb1Ac of patients were significantly reduced after surgical and non-surgical periodontal therapy, where both behaved similarly when compared to each other, but with greater effectiveness of surgical therapy in reducing the studied clinical parameters. The precise mechanisms that lead to HbA1c reduction and improved glycemic control after periodontal treatment in people with diabetes are not completely clear, but are presumed to arise from the combined effects of reduced systemic inflammation and reduced systemic bacterial challenge, leading to improvements in insulin resistance and insulin signaling (POLACK and SHAPIRA, 2018) [37] .…”
Section: Diabetes and Periodontitismentioning
confidence: 99%
“…This is a chronic metabolic disorder associated with long-term smash up, dysfunction, and malfunction of different organs, in particular, the eyes, kidneys, nerves, blood vessels, and heart. That creates systemic complications and it is one of the leading causes of morbidity and mortality worldwide in affected persons [2,3].…”
Section: Introductionmentioning
confidence: 99%